The Implementation of Three-Dimensional Figures in Learning Social Lessons to Improve the Learners' Cognition - Irma Sofiasyari; Iin Indrianti (Jurnal Elementaria Edukasia, 2024)
The use of learning media that is less interactive can cause students' cognitive deficiencies. Therefore, innovation is needed to use learning media that can improve students' cognitive abilities. Another fact is that the learning process only focuses on the teacher, so learning looks monotonous. So, based on the results of these observations, the research aims to improve the cognitive outcomes of elementary school students in social studies learning at SDN A Indramayu. This research is classroom action research, using the Kemmis & MC Taggart model, which applies 3 cycles. Data collection techniques use tests, observations, field notes, and documentation. The data analysis techniques used are quantitative and qualitative. Qualitative analysis applies to students' cognitive test results each cycle while qualitative analysis applies to observation results. The research results show that the use of three-dimensional media can improve the cognitive outcomes of class IV students at SDN A Indramayu. The research evidence is that the increase from pre-cycle to cycle I increased by 20.24%, from cycle I to cycle II by 15.34%, and from cycle II to cycle III by 5%. Based on the research results, it can be concluded that class IV students at SDN A Indramayu can improve their cognitive abilities by implementing three-dimensional media in social studies learning. Penggunaan media pembelajaran yang kurang interaktif dapat menyebabkan kurangnya kognitif siswa. Maka dari itu, diperlukan inovasi untuk menggunakan media pembelajaran yang dapat meningkatkan kognitif siswa. Fakta yang lain, dalam proses pembelajaran hanya berpusat kepada guru, sehingga pembelajaran terlihat monoton. Berdasarkan hasil observasi tersebut, penelitian bertujuan untuk meningkatkan hasil kognitif siswa sekolah dasar pada pembelajaran IPS di SDN A Indramayu. Penelitian ini merupakan penelitian tindakan kelas, menggunakan model Kemmis & MC tagart, yang menerapkan 3 siklus. Tenik pengumpulan data menggunakan tes, pengamatan, catatan lapangan, dan dokumentasi. Teknik analisis data yang digunakan yaitu secara kuantiatif dan kualitatif. Analisis kualitatif berlaku untuk hasil tes kognitif siswa setiap siklus sementara analisis kualitatif berlaku untuk hasil observasi. Hasil penelitian menunjukkan penggunaan media tiga dimensi mampu meningkatkan hasil kognitif siswa kelas IV SDN A Indramayu. Bukti penelitian tersebut adalah peningkatan dari pra siklus ke siklus I meningkat sebesar 20,24%, dari siklus I ke siklus II 15,34% dan dari siklus II ke siklus III 5%. Berdasarkan hasil penelitian, dapat disimpulkan siswa kelas IV SDN A Indramayu kognitifnya dapat meningkat dengan mengimplementasikan media tiga dimesi dalam pembelajaran IPS